PENAFSIRAN REKAMAN SEISMIK PANTUL DANGKAL SALURAN TUNGGAL DI PERAIRAN KABAENA, MUNA DAN BUTON, SULAWESI TENGGARA - Astawa, I Nyoman; Astjario, P.; K.G. Aryawan, I. (Jurnal Geologi dan Sumberdaya Mineral, 2007)
East Sulawesi terrane, generally called East Sulawesi Ofiolite, consists of ultramafic rock underlying pelagic sediment as a top layer. The rock is interpreted as a basement rock in  the East Sulawesi  Terrane which was formed during early Cretaceous. This ultramafic rock tectonically contacted with Mesozoicum and Paleogen ones, and unconformably overlied by molasses sediment type on the top.A number of single channel seismic profiling has been carried out and passing through between Kabaena, Muna and Buton islands.  Based on outcropping  and distribution  of rock units on those three islands, the seismic lines were made to get a clear geological  setting under the seafloor. Differentiation  of internal configuration  reflector of the seismic  records which  Interrelated  to rock unit on the islands have been interpreted very clearly. The study of seismic single channel records will be more accurate if it is correlated to the offshore drilling data in order to make an estimation of internal configuration reflectors to be definitely  correct. Keywords:  terrane, tectonic, seismic, interpretation, Buton